Persistent conditioned place preference to cocaine and withdrawal hypo-locomotion to mephedrone in the flatworm planaria. (23rd April 2015) - Hutchinson, Claire V; Prados, Jose; Davidson, Colin
Highlights: We show conditioned place preference in planaria to cocaine. We find long-lasting hypo-motility to mephedrone. We have used clinically relevant concentrations. Abstract: The purpose of the present study was to determine the effects of exposure to cocaine and mephedrone on conditioned place preference (CPP) and locomotion in the flatworm planaria. Planaria were treated with either cocaine or mephedrone at 1 or 10 μM. Planaria were exposed to 15 min of drug in their non-preferred place (either a rough- or smooth-floored petri dish) on alternate days, and were exposed to normal water in their preferred place on the following day. There were 5 days of conditioning to drug. Planaria were then tested for CPP on day 2, 6 and 13 after withdrawal. We found that animals exhibited CPP to cocaine at both 1 and 10 μM, but not to mephedrone. When examining locomotor activity we found that neither cocaine nor mephedrone treatment showed any evidence of evoking increased motility or locomotor sensitisation. Hypo-motility was seen on the first day of conditioning at concentrations of 10 μM for both cocaine and mephedrone, but had disappeared by the last day of conditioning. Examining chronic withdrawal, only 10 μM mephedrone had a significant effect on motility, decreasing locomotion on day 2 of withdrawal. Taken together we have shown that cocaine evoked CPP in planaria. We have also shown withdrawal depressing effects of mephedrone on motility.